2021
DOI: 10.3389/fpls.2020.627969
|View full text |Cite
|
Sign up to set email alerts
|

Plant Hormone-Mediated Regulation of Heat Tolerance in Response to Global Climate Change

Abstract: Agriculture is largely dependent on climate and is highly vulnerable to climate change. The global mean surface temperatures are increasing due to global climate change. Temperature beyond the physiological optimum for growth induces heat stress in plants causing detrimental and irreversible damage to plant development, growth, as well as productivity. Plants have evolved adaptive mechanisms in response to heat stress. The classical plant hormones, such as auxin, abscisic acid (ABA), brassinosteroids (BRs), cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(137 citation statements)
references
References 106 publications
1
114
0
1
Order By: Relevance
“…A series of physiological and ecological changes occur in plants due to high temperatures, affecting their growth and development [147]. Heat stress can result in a serious decline in agricultural economic yield due to adverse effects on crop physiology, including cell membrane damage, enzyme inactivation, inhibition of photosynthesis, and enhanced respiration [148,149].…”
Section: Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of physiological and ecological changes occur in plants due to high temperatures, affecting their growth and development [147]. Heat stress can result in a serious decline in agricultural economic yield due to adverse effects on crop physiology, including cell membrane damage, enzyme inactivation, inhibition of photosynthesis, and enhanced respiration [148,149].…”
Section: Heat Stressmentioning
confidence: 99%
“…However, the mechanisms underlying heat response pathway interactions with JA are rarely explored [155]. Several studies have suggested that JA might regulate plant heat stress responses through a subset of the WRKY superfamily that is induced by JA [149,156,157].…”
Section: Heat Stressmentioning
confidence: 99%
“…3 D). Considering V14 might act via phytohormone-mediated thermosensory pathways [ 48 , 49 ], we examined the response of v14 seedlings to various phytohormone treatments (Additional file 8 ). However, none of such treatments could restore the albinism observed at 25 °C, suggesting that V14 is irresponsive to phytohormones.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an increased protein metabolism in these organs. It is believed that the stress response is transitory and ensures the transition of the plant from normal to stressful metabolism by blocking non-essential metabolic pathways and triggering protective mechanisms, especially shock response systems (Waters & Vierling, 2020;Li et al, 2021). The increase of protein content in roots and rhizomes may be a consequence of their enzymatic adaptation and compaction of membrane structures in order to protect cells against the damaging factor.…”
Section: Discussionmentioning
confidence: 99%